Design of a powered full-body exoskeleton for physical assistance of elderly people. (10th November 2021) - Christensen, Simon; Rafique, Sajid; Bai, Shaoping
The development of full-body exoskeletons has been limited due to design complexities, mechanical integration intricacies, and heavier weight, among others. Consequently, very few full-body powered exoskeletons were developed to address these challenges, in spite of increasing demand for physical assistance at full-body level. This article presents an overall design and development of a powered full-body exoskeleton called "FB-AXO." Primarily, FB-AXO consists of two main subsystems, a lower-body and an upper-body subsystem connected together through waist and spine modules. FB-AXO is developed for the support of weaker ageing adults so that they can continue functioning their daily activities. At the onset of the project, a set of functional and design requirements has been formulated with an extensive end-user involvement and then used in realizing the FB-AXO. The final FB-AXO design comprises of 27 degrees of freedom, of which 10 are active and 17 are passive, having a total system weight of 25 kg. Overall, the article elaborates comprehensively the design, construction, and preliminary testing of FB-AXO. The work effectively addresses design challenges including kinematic compatibility and modularity with innovative solutions. The details of the mechanics, sensors, and electronics of the two subsystems along with specifics of human-exoskeleton interfaces and ranges of motion are also provided. The FB-AXO exoskeleton effectively demonstrated to assist full-body motions such as normal walking, standing, bending as well as executing lifting and carrying tasks to meet the daily living demands of older users.